2009
DOI: 10.1681/asn.2007080837
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Increases Risk of ESRD among Elderly

Abstract: Risk for ESRD among elderly patients with acute kidney injury (AKI) has not been studied in a large, representative sample. This study aimed to determine incidence rates and hazard ratios for developing ESRD in elderly individuals, with and without chronic kidney disease (CKD), who had AKI. In the 2000 5% random sample of Medicare beneficiaries, clinical conditions were identified using Medicare claims; ESRD treatment information was obtained from ESRD registration during 2 yr of follow-up. Our cohort of 233,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
790
1
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,019 publications
(835 citation statements)
references
References 30 publications
30
790
1
14
Order By: Relevance
“…As the evidence linking AKI with loss of kidney function [45][46][47][77][78][79][80] , hypertension 81,82 , cardiovascular disease 49,50,83 , and death 46,[83][84][85][86][87] accumulates, determining the optimal care for this growing population is critical. The American Society of Nephrology AKI Advisory Group has highlighted the transition of care as a potential opportunity to reduce the long-term impact of AKI 88 , and hence, AKD.…”
Section: Follow-up Carementioning
confidence: 99%
“…As the evidence linking AKI with loss of kidney function [45][46][47][77][78][79][80] , hypertension 81,82 , cardiovascular disease 49,50,83 , and death 46,[83][84][85][86][87] accumulates, determining the optimal care for this growing population is critical. The American Society of Nephrology AKI Advisory Group has highlighted the transition of care as a potential opportunity to reduce the long-term impact of AKI 88 , and hence, AKD.…”
Section: Follow-up Carementioning
confidence: 99%
“…In addition, several adult studies have demonstrated a dose-response relationship between AKI and CKD, including a higher risk of CKD in those with more severe AKI and also in those with repeated episodes of AKI [35][36][37]. Several pediatric observational studies have also shown a high proportion of CKD in survivors of AKI, ranging from 10 to 69%, but these studies have focused on populations without primary kidney disease [38][39][40][41][42][43][44].…”
Section: Aki and Ckd Associationmentioning
confidence: 99%
“…14 Incomplete or partial recovery of kidney function following AKI is likely to become an increasingly recognized problem, and data suggest these patients also have a lower rate of survival and a higher risk of progression to ESKD. 15,16 An estimated 30% of all critically ill patients have premorbid CKD. 8,17 In patients with a superimposed episode of AKI on CKD, there is a high risk of non-recovery and accelerated progression to ESKD.…”
Section: Lengths Of Staymentioning
confidence: 99%